Journey down the years - Bond, Ruskin (New Delhi Rupa publications, 2017)
As a novelist and storyteller, I have always drawn upon my memories of places that I have known and lived in over the years. More than most writers, perhaps, I find myself drawing inspiration from the past$1 (Bmy childhood, adolescence, youth, early manhood.. The stories and the poems float in through my window, float in from the magic mountains and the words appear on the page without much effort on my part.Ruskin Bond has been writing for over sixty years, in the course of which he has come to be known for his simple and witty writing style. These twenty-five stories form a delightful collection of some of his non-fiction sketches, his interaction with the natural world and his life in small towns that has given him some of his biggest stories.Bond$1 (Bs journey as a writer has been a remarkable one and these stories show the master storyteller at his very best.s
Keywords: Anthology